Amblyomma sp. infestation on a Javan Pangolins (Manis javanica) at the Cikananga Wildlife Center - Tetty Barunawati Siagian; Muhamad Fikri; Wahyu Wahyu; Inna Rakhmawati (ARSHI Veterinary Letters, 2024)
Javan Pangolins in ex-situ conservation are vulnerable to tick infestations. This study aimed to identify the tick species infesting three female Javan Pangolins at the Cikananga Wildlife Center, all confiscated by the Conservation Area Management in Sukabumi, Indonesia, from wildlife trafficking. One pangolin had a documented history of tick infestation. Tick collection involved carefully handling and restraining the pangolins, opening their scales, and applying cotton soaked in 70% alcohol to the infested areas for five minutes. The ticks were removed with anatomical tweezers and preserved in 70% alcohol. Microscopic identification at 100x magnification revealed the ticks to be Amblyomma sp., characterized by a rectangular capitulum base, long slender palpi, an anal ridge and groove, and 13 festoons. This study concludes that the ticks infesting Javan Pangolins at the Cikananga Wildlife Center belong to the Amblyomma species, highlighting the importance of ongoing monitoring and management of ectoparasites in conservation environments.